Emotional Reactivity and Regulation in Preschool-Age Children Who Do and Do Not Stutter: Evidence From Autonomic Nervous System Measures - Tumanova, Victoria; Wilder, Blair; Gregoire, Julia; Baratta, Michaela; Razza, Rachel (Frontiers in Human Neuroscience, 2020)
We examined the emotional reactivity and emotion regulation in preschool-age children who do (CWS) and do not stutter (CWNS) by assessing their psychophysiological response during rest and while viewing pictures from the International Affective Picture System (Lang, Bradley & Cuthbert, 2008). Participants were 18 CWS (16 boys and 2 girls; mean age 4 years, 5 months) and 18 age- and gender-matched CWNS. Participants’ psychophysiological responses were measured during two baselines and two picture viewing conditions. Skin conductance level (SCL) and heart rate were measured to assess emotional reactivity. Respiratory sinus arrhythmia (RSA) was measured to assess emotional regulation. Participants’ shyness and executive function were assessed via parent report and considered for their effects on participants’ psychophysiological responses. Results: First, CWNS and CWS did not differ in their initial baseline SCL, heart rate, or RSA, but all participants had higher SCL and lower RSA in the second baseline, subsequent to the first challenge condition, compared to the first baseline. Second, during the challenge conditions, CWS did not differ from CWNS in their SCL, but showed a significantly higher heart rate than CWNS. Third, CWS exhibited a significantly lower RSA during the challenge conditions compared to CWNS. Lastly, shyness was associated with preschool-age children’s SCL, such that participants who were rated higher in shyness had a higher SCL during the challenge conditions. Participants’ executive function had a marginally significant effect on the RSA, such that the participants who had higher executive function composite scores exhibited lower RSA during the challenge conditions. Conclusions: Our findings suggest that CWS and CWNS did not differ in their emotional reactivity and emotional regulation abilities at rest. During challenge conditions, however, CWS tended to be more emotionally reactive, as indicated by a higher heart rate, and also employed more emotional regulation, indexed by a greater decrease in RSA, compared to CWNS. Preschool-age children’s behavior is largely dominated by reactivity, but there is the emergence of regulation, which can help children adjust to various contextual demands. For CWS who are more emotionally reactive, regulatory skills may be particularly critical to their prognosis and treatment.